Landscapes of human evolution : contributions in honour of John Gowlett - Cole, James,; McNabb, John,; Grove, Matt,; Hosfield, Robert,; Gowlett, John, (Archaeopress Archaeology, 2020)
Fourteen papers are presented here in honour of John Gowlett. John has a wide range of research interests primarily focused on the human genus Homo and is a world leader in understanding the cognitive and behavioural preconditions necessary for the emergence of complex behaviours such as language and art.